قيام المراجعين الداخليين بمراجعة مكاتب ضمان الجودة وتقييم الأداء في الجامعات الليبية - امجاور, فجرية بوبكر; مرسال, . فريحة عبدالقادر (Tobruk University Journal of Social and Human Sciences, 2024)
The quality of Libyan university education depends on continuous development and improvement, which is supposed to be the source and pillar of the quality assurance and performance evaluation offices, and responsible for implementing everything mentioned in the guide of the Center for Quality Assurance and Performance Evaluation in these universities; to obtain programmatic and institutional accreditation, but these offices are still below the required level; therefore it has becomeIt is essential for internal auditors to review the quality assurance and performance evaluation offices in Libyan universities, to reflect the external perspective, and to succeed and enhance the quality philosophy and practice in Libyan universities. This study aimed to present a proposed vision for internal auditors to review the quality assurance and performance evaluation offices in Libyan universities. To achieve the study's objectives, the following were relied upon The descriptive approach was adopted due to its suitability to the nature of the study, through a review and analysis of theoretical literature, to achieve the study's objectives. The study reached a set of results, the most important of which are: Internal audit is one of the functions of modern academic administration, its path towards quality, and the enhancement of its philosophy and practice in Libyan universities. Internal audit has a significant impact on quality assurance and performance evaluation offices The more thorough the review process is in its inspection and follow-up, the more clearly and clearly this reflects in the universities' ability to obtain accreditation. The study also recommended a set of recommendations, the most important of which is that internal audits should have positive effects when reviewing quality assurance and performance evaluation offices, perhaps most notably qualifying them for accreditation from the National Center for Quality Assurance and Performance Evaluation